2001
DOI: 10.1002/hed.10027
|View full text |Cite
|
Sign up to set email alerts
|

Neutron radiotherapy for recurrent pleomorphic adenomas of major salivary glands

Abstract: Neutron radiotherapy offers both excellent local control rates and survival rates in patients with multiply recurrent pleomorphic adenomas that are not candidates for surgical resection, even in the presence of gross residual disease. The treatment-related morbidity is acceptable. Malignant transformations and metastases, although uncommon, may be observed in this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
(18 reference statements)
1
21
0
1
Order By: Relevance
“…The 10-year relapse-free survival rates were 62% for those treated with radiation for gross disease compared with 93% for those treated for subclinical disease (P ϭ 0.0005). Douglas et al 14 reported on 16 patients treated with neutron RT at the University of Washington (Seattle) between 1986 and 1993 and had a median follow up of 83 months. Ten patients had gross disease and 6 had subclinical disease at the time of RT.…”
Section: Discussionmentioning
confidence: 98%
“…The 10-year relapse-free survival rates were 62% for those treated with radiation for gross disease compared with 93% for those treated for subclinical disease (P ϭ 0.0005). Douglas et al 14 reported on 16 patients treated with neutron RT at the University of Washington (Seattle) between 1986 and 1993 and had a median follow up of 83 months. Ten patients had gross disease and 6 had subclinical disease at the time of RT.…”
Section: Discussionmentioning
confidence: 98%
“…Douglas et al 25 reported on 16 patients with recurrent and/or unresectable pleomorphic adenoma treated between 1986 and 1993 with neutron RT at the University of Washington (Seattle, WA). Indications for RT included gross residual disease, 10 patients; indeterminate margins, 2 patients; and/or multinodular recurrence, 9 patients.…”
Section: Radiotherapymentioning
confidence: 97%
“…Entretanto, não foi observada recidiva dos tumores considerados primários em nosso estudo, com acompanhamento mínimo de 38 meses e máximo de cinco anos. Esse fato pode ser atribuído ao tratamento cirúrgico com remoção total da glândula salivar acometida, aplicado à maioria dos tumores no HCP e preconizado na literatura (8,16,33) .…”
Section: Discussionunclassified